Sickle cell trait: A review and recommendations for training - Fidler, E. (Strength and Conditioning Journal, 2012)
Sickle cell trait (SCT) is a common genetic condition that is generally benign; however, under extreme physical exertion, catastrophic complications can occur. Unfortunately, many people do not know that they are a carrier, and symptoms can easily be confused with more common conditions, making it hard to recognize immediately. Sickling injuries in athletics can easily be prevented through screening, education, and proper acclimation to activity. This article is a review of the physiology behind SCT and offers recommendations for the prevention and management of a collapse.